2020
DOI: 10.1186/s12891-020-3109-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between acromiohumeral distance and the severity of supraspinatus tendon tear by ultrasound imaging in a Chinese population

Abstract: Background: The aim of this study was twofold: (i) to investigate the intrarater reliability of acromiohumeral distance measurement; (ii) to assess the level of association between acromiohumeral distance measured by ultrasonography, and the degree of supraspinatus tendon tear, in patients suffering from chronic shoulder pain. Methods:A cross-sectional, case-control study was carried out. A convenience sample comprising 59 patients with a unilateral supraspinatus tendon tear was assessed. Both shoulders of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…SIS is a dysfunction where mechanical compression of the rotator cuff structures (muscles and bursa) occurs due to obliteration in the subacromial space [1,2]. SIS is characterised by a painful arc of motion during elevation and is the foremost cause of years with disability [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIS is a dysfunction where mechanical compression of the rotator cuff structures (muscles and bursa) occurs due to obliteration in the subacromial space [1,2]. SIS is characterised by a painful arc of motion during elevation and is the foremost cause of years with disability [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Of all reported shoulder injuries, SIS accounts for 27% of the injury burden in overhead athletes [3]. Acromiohumeral distance (AHD) is considered a good indicator of the subacromial space, and it is defined as the space between the superior humeral edge and the lateral most portion of the acromion [2]. In an anatomical position, a normal AHD measurement ranges from 8-13mm with limited physiologic decrease, even on shoulder elevation [5].…”
Section: Introductionmentioning
confidence: 99%
“…One measurement that is commonly used in radiology to help indicate rotator cuff pathology is the acromiohumeral distance (AHD). Prior literature has shown that a narrower AHD is indicative of rotator cuff pathology and shoulder impingement symptoms in a cohort of nonwheelchair users 34,35 . Although AHD is not typically measured as part of a standard of care ultrasound examination, recent studies have shown that ultrasound can reliably measure this feature 34‐43 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature has shown that a narrower AHD is indicative of rotator cuff pathology and shoulder impingement symptoms in a cohort of nonwheelchair users. 34,35 Although AHD is not typically measured as part of a standard of care ultrasound examination, recent studies have shown that ultrasound can reliably measure this feature. [34][35][36][37][38][39][40][41][42][43] Mean normal value of AHD has previously been established at 1.09 cm (SD: .42 cm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation